GROUP GUIDANCE AND READINESS OF STUDENTS PARTICIPATE IN UJIAN NASIONAL (UN) - Nirwana, Herman (Universitas Muhammadiyah Metro, 2013)
Abstract: National Exam (UN) is an instrument for evaluation of learning outcomes that are conducted every year, and the result is used as an indicator in determining the quality of education an educational unit. Various businesses or process improvements that have been made to prepare students to face the UN, but the results have not been quite encouraging. This is because the program is designed for this more focused on preparing students in the mastery of the subject matter while the mental preparation of the students in the exam has not received attention optimal. One of the counseling services that can be given to students to mentally prepare them for exams is group counseling services. In this article, mentally preparing students for exams through group counseling are discussed.Keyword: Readiness, students, group guidance.